Systems genetic and pharmacological analysis identifies candidate genes underlying mechanosensation in the von Frey test. (5th July 2016) - Young, E. E.; Bryant, C. D.; Lee, S. E.; Peng, X.; Cook, B.; Nair, H. K.; Dreher, K. J.; Zhang, X.; Palmer, A. A.; Chung, J. M.; Mogil, J. S.; Chesler, E. J.; et al.
Abstract : Mechanical sensitivity is commonly affected in chronic pain and other neurological disorders. To discover mechanisms of individual differences in punctate mechanosensation, we performed quantitative trait locus (QTL) mapping of the response to von Frey monofilament stimulation in BXD recombinant inbred (BXD) mice. Significant loci were detected on mouse chromosome (Chr) 5 and 15, indicating the location of underlying polymorphisms that cause heritable variation in von Frey response. Convergent evidence from public gene expression data implicates candidate genes within the loci: von Frey thresholds were strongly correlated with baseline expression of Cacna2d1, Ift27 and Csnk1e in multiple brain regions of BXD strains. Systemic gabapentin and PF‐670462, which target the protein products of Cacna2d1 and Csnk1e, respectively, significantly increased von Frey thresholds in a genotype‐dependent manner in progenitors and BXD strains. Real‐time polymerase chain reaction confirmed differential expression of Cacna2d1 and Csnk1e in multiple brain regions in progenitors and showed differential expression of Cacna2d1 and Csnk1e in the dorsal root ganglia of the progenitors and BXD strains grouped by QTL genotype. Thus, linkage mapping, transcript covariance and pharmacological testing suggest that genetic variation affecting Cacna2d1 and Csnk1e may contribute to individual differences in von Frey filament response. This study implicates Cacna2d1 and Ift27 in basal mechanosensation in line with their previously suspected role in mechanical hypersensitivity. Csnk1e is implicated for von Frey response for the first time. Further investigation is warranted to identify the specific polymorphisms involved and assess the relevance of these findings to clinical conditions of disturbed mechanosensation. Abstract : Two QTL, on chr 5 and 15, were identified for mechanosensation using the BXD RI strain panel. Candidate gene testing supports a role for Cacna2d1 (chr 5) and Csnk1e (chr 15) in mechanosensation variability.